Ownership, Access, and Sequential Investment. (February 2014) - Mai, Maxim; Smirnov, Vladimir; Wait, Andrew
Abstract We extend the property‐rights framework to allow for a separation of the ownership rights of access and veto and for sequential investment. Parties investing first do so before contracting is feasible. It is possible, however, that parties investing second can share (at least some of) their investment costs. Along with this cost‐sharing effect, the incentive to invest is affected by a strategic effect generated by sequential investment. Together these effects can overturn some of the predictions of the property‐rights literature. For example, the most inclusive ownership structure might not be optimal, even if all investments are complementary.